Pengaruh Ukuran Partikel dan Lama Ekstraksi terhadap Karakteristik Ekstrak Pewarna Alami Daun Pandan Wangi (Pandanus amaryllifolius R.) - Sayoga, Made Hary; Wartini, Ni Made; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 2 (2020): Juni, 2020)
Fragrant pandan leaves can be used as a natural coloring because they contain chlorophyll obtained through the extraction process. The purposes of this study were to determine the effect of particle size and extraction time on the characteristics of natural pandanus fragrance leaf extract and determine the best treatment of particle size and extraction time to produce natural pandanus leaf extract dye. This study used a 2 factorial factorial randomized block design. The first factor is the particle size which consists of 3 levels, namely 40, 60, 80 mesh. The second factor is the extraction time which consists of 3 levels, namely 24, 36, and 48 hours. The results showed that the treatment of particle size and extraction time affected the yield, chlorophyll a, chlorophyll b, total chlorophyll, brightness (L *), redness (a *) and yellowish level (b *). The treatment of 60 mesh particle size and 36 hour extraction time are the best treatment to produce natural pandanus fragrance extract coloring with yield characteristics of 8.81% chlorophyll a level of 23.66%, chlorophyll b level of 3.92%, total chlorophyll content of 27.57%, the brightness level (L *) 21.06, the redness level (a *) 4.92, the yellowish level (b *) 6.21. Keywords: Pandanus amaryllifolius R., chlorophyll, color, extraction